Invasive Fungal Disease Among Pediatric and Adolescent Patients Undergoing Itraconazole Prophylaxis After Hematopoietic Stem Cell Transplantation - Suluk Itsaradisaikul (2022)
Background: Invasive fungal disease (IFD) is a major cause of morbidity and mortality in patients after hematopoietic stem cell transplantation (HSCT). Itraconazole has been used for prevention of IFD, but data related to incidence and associated factors of IFD in pediatric and adolescent patients on itraconazole prophylaxis remain scarce. Objectives: To identify incidence and risk factors associated with IFD among pediatric and adolescent patients receiving itraconazole prophylaxis after HSCT. Methods: Patients younger than 21 years who received itraconazole prophylaxis after HSCT from January 2007 to December 2016 were retrospectively enrolled. Incidence of IFD within 1 year and associated factors were analyzed. Results: All patients received itraconazole during the pre-engraftment period. Of 170 patients, 29 had IFD, with an incidence of 17.1% at 1 year. IFD at 1 year was significantly associated with increased mortality. Of 29 patients with IFD, only 9 developed IFD while on itraconazole prophylaxis (5.3%), all of whom had invasive pulmonary aspergillosis. No invasive candidiasis occurred during itraconazole prophylaxis. Prolonged neutropenia (hazard ratio [HR] = 1.08; 95% confidence interval [CI], 1.02-1.13), graft-versus-host disease within 100 days after transplantation (HR = 3.17; 95% CI, 1.17-8.57), and using etoposide in preconditioning regimens (HR = 21.60; 95% CI, 2.44-190.95) were significantly associated with IFD at 1 year. No patients had to discontinue itraconazole because of its adverse effects. Conclusions: Itraconazole proffered good efficacy for prevention of candidiasis during the pre-engraftment period. Most IFD episodes occurred after the engraftment period when itraconazole had been discontinued. During this period, patients with risk factors require appropriate fungal prophylaxis.